Design of an Automated Fasteners Sorting Machine for Accurate Types and Sizes Differentiation in Assembly Lines. - JUN JIN, ENG; Azlan, Mohd Azwir; Idris, Ahmad Fu'ad (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This project addresses the critical need for efficient and accurate fastener sorting (bolts, nuts, washers) in industries like automotive, aerospace, electronics, construction, and machinery, where manual processes are slow and error-prone. The primary goal was to design a compact, portable automated machine capable of accurately identifying and sorting up to 18 different fastener types by size and type. Methodologically, a systematic design process utilized SolidWorks for 3D modeling and simulation, resulting in a machine engineered with parameters to maximize sorting speed and minimize manual work; its core feature is an automated mechanism using advanced algorithms for precise recognition and categorization, significantly reducing errors. Findings demonstrate high sorting accuracy, boosting assembly line productivity, with a durable, corrosion-resistant design ensuring longevity in industrial settings; the machine is projected to streamline production by drastically cutting sorting times and enhancing overall operational efficiency. In conclusion, this project successfully proves the feasibility of a compact automated sorter suitable for small-to-medium industries, offering a practical solution to revolutionize fastener management by overcoming manual inefficiencies and leading to substantial gains in productivity and operational effectiveness. The automated fastener sorting machine weighs 31.925 kg and has dimensions of 1014.83 mm (L) × 1694.25 mm (W) × 1003.94mm(H).